Response of small scale ultra high performance fibre reinforced concrete slabs to blast loading. (15th September 2015) - Mao, L.; Barnett, S.J.; Tyas, A.; Warren, J.; Schleyer, G.K.; Zaini, S.S.
Highlights: The paper provides a systematic study of the performance of UHPFRC slabs under close-in explosions. Field tests show behaviour UHPFRC slabs under close-in explosion and corresponding crack pattern. Performance of UHPFRC slabs under explosion can be simulated with good quality using numerical model. Abstract: This paper provides a systematic study of the performance of ultra high performance fibre reinforced concrete (UHPFRC) slabs under close-in explosions. In the study, the UHPFRC slabs were manufactured with varying amounts and types of steel fibres. In field tests, various PE4 charge sizes were employed to generate blast load until a sudden increase in maximum deflection was observed. Peak 1/4 span deflections and development of slab cracks were recorded. With the results, the effect of steel fibres on performance of UHPFRC slabs can be better clarified. Static tests were also used to study the effect of fibres on the behaviour of UHPFRC specimens, results indicate that fibre distribution and orientation can clearly affect UHPFRC slab behaviour. Finally, finite element modelling was employed to simulate the performance of UHPFRC slabs under blast loading and these modelling results were compared to test data. Based on the comparison results, potential further enhancement of numerical models is discussed.